Dilema Etika dalam Penelitian dan Pendidikan Lingkungan - Abdul Rasyid Fakhrun Gani; Andi Basliahwanti Murti; Devi Alvionita (Jurnal Pendidikan Biologi undiksha, 2021)
Environmental problems are a major threat to human survival. Humans have created agencies and institutions that manage the environment, but there are still human activities that have a big impact on the environment, such as the large number of jobs that make environmental conditions worse. These problems cause ethical dilemmas in environmental research. Gaps in research and scientific ethics are important issues in the environmental field. To make ends meet, humans do not need to sacrifice their environment. To solve environmental problems requires natural science and technology combined with ethics to maximize these goals. This article is written as a solution to develop human morality and awareness by researching the following environmental ethics. Increasing the level of awareness can help increase human compliance in implementing laws related to environmental protection. Based on literature studies, current environmental problems can be overcome by changing the way humans perceive and behave towards nature. Ethical dilemmas in environmental research can be overcome by 1) efforts to improve morale, ethics and environmentally friendly research actions, 2) the importance of environment-based education and learning, and 3) environmental impact analysis (AMDAL).